Collectibility Analysis for Small and Medium Enterprise â€“ Bank BUKOPIN Case - Koesrindartoto, Deddy P.; Pratiwi, Mega (School of Business and Management Institut Teknologi Bandung, 2010)
In Indonesia, small and medium enterprises (SME) have experienced 68% growth in 2008 and47% growth in 2007. The simple structure made it able to respond quickly to changingeconomic conditions and meet local customersâ€™ needs, growing sometimes into large andpowerful corporations or failing within a short time of the firmâ€™s inception. Unfortunately,lack of access to finance has been cited as an important problem for SMEs, being theconstraint in the creation, development or diversification of their economic activities. Lendinginstitution such as banks conduct an intensive assessment (usually called credit scoring) tofind out the creditworthiness of applicants in order to mitigate the risk. This paper,â€œCollectability Analysis in Small and Medium Enterpriseâ€, is purposed for creatingappropriate credit scoring model to support the judgmental analysis approach in small andmedium enterprise, finding out how generic and plafond-specific variables affect thecollectability of the debtors from different plafond level (< Rp. 500 Million and > Rp. 500Million), and providing early detector for the bank to predict about future loan performanceof its debtors, thus the bank can be more careful in selecting qualified debtors.Key words: small and medium enterprises, credit rating, loan plafond, collectability, genericvariables, plafond-specific variables.